2023
DOI: 10.3389/fmars.2022.1038463
|View full text |Cite
|
Sign up to set email alerts
|

Larval dispersal patterns and connectivity of Acropora on Florida’s Coral Reef and its implications for restoration

Abstract: Since the 1980s, populations of Acropora cervicornis and A. palmata have experienced severe declines due to disease and anthropogenic stressors; resulting in their listing as threatened, and their need for restoration. In this study, larval survival and competency data were collected and used to calibrate a very high-resolution hydrodynamic model (up to 100m) to determine the dispersal patterns of Acropora species along the Florida’s Coral Reef. The resulting connectivity matrices was incorporated into a metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In this study, we have shown that, all other things being equal, the spatial resolution of a biophysical model influences the resulting dispersal patterns and connectivity metrics. We therefore suggest that the scale at which a model can provide recommendations for reef management, for example regarding the delineation of Marine Protected Areas 47 , 48 or the identification of the most suitable reefs for restoration measures 49 , 50 , can not be finer than its spatial resolution. Any recommendation based on model results is therefore valid and applicable at scales coarser than that resolution.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In this study, we have shown that, all other things being equal, the spatial resolution of a biophysical model influences the resulting dispersal patterns and connectivity metrics. We therefore suggest that the scale at which a model can provide recommendations for reef management, for example regarding the delineation of Marine Protected Areas 47 , 48 or the identification of the most suitable reefs for restoration measures 49 , 50 , can not be finer than its spatial resolution. Any recommendation based on model results is therefore valid and applicable at scales coarser than that resolution.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…When competent larvae are over a reef, we assume they can settle at a rate 20% per hour based on larval vertical swimming speed, as in King et al. (2023).…”
Section: Methodsmentioning
confidence: 99%
“…20% per hour based on larval vertical swimming speed, as inKing et al (2023).Finally, once all the necessary parameters were set, virtual particles were released on all FCR reefs. The reef shapefile used to locate the different reefs in FCR was extracted from the "coral reefs and hardbottom" layer of the Unified Florida Reef Tract Map (Florida Fish and Wildlife Conservation Commission-Fish and Wildlife Research Institute, 2017).…”
mentioning
confidence: 99%
“…These are both facilitated by regional circulation patterns and the spatial orientation of a reef (Holstein et al, 2014; Leichter et al, 2013). Recruitment is a primary driver of coral reef recovery from disturbance (Holbrook et al, 2018), and connectivity is an important input into selection of restoration sites and species composition of coral outplants (Figure 3; King et al, 2023). Some potential restoration sites may be more likely to consistently attract and retain larvae (or sustain local coral species that have short pelagic durations) than other sites, increasing the probability of self‐sustaining coral populations.…”
Section: Coral Restoration For Coastal Protectionmentioning
confidence: 99%